The Role of Medan Regulatory Assistance Institute (LBH) in Handling Alleged Malpractice Crimes of Assistant Pharmacists Based on the Perspective of Fiqh Siyasah Maliyah - Muhammad Rafhi Rs; Irwansyah Irwansyah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The presence of legal aid is considered very important for countries that use equality before the law guidelines. So far, the provision of legal aid has not been seen as significant in reaching poor people or groups. This kind of research needs to be done to provide information and education to the wider community that there is still justice being created in this country. This research is qualitative research, using an empirical juridical analysis approach to research aspects. The data collection technique of this research is by document study method, more precisely using secondary documents in the form of case files during this case, then by structured interview technique whose sources are LBH Medan volunteers and Okta and Sukma, and finally by literature study technique. The end of all the struggles of LBH Medan volunteers was determined by the Panel of Judges of Medan District Court by handing down a verdict of acquittal (vrijspraak) in case Number 2258/Pid. Sus/2020/PN Mdn and also the Panel of Judges restored the rights of the defendant from all legal charges. There are several considerations presented by the Panel of Judges in the acquittal (vrijspraak) in this case, that it was not Okta and Sukma who made the mistake of giving drugs but Endang Batubara. In this case, in terms of state expenditure through the provision of food and drink as well as vitamins and supporting equipment while in prison, it has spent a lot of budgets with the fact that the case was forced like this. As a result, the state can spend to provide for the needs of Okta and Sukma while imprisoned around Rp. 30,000,000 (Thirty Million Rupiah) in a period of 4 months of detention.